Transformation of International Criminal Justice Principle into Indonesia National Criminal Justice System: How Domestic Law Adopt Global Values? - Amandha, Asyaffa Ridzqi; Arifin, Ridwan; Rahmayani, Chanidia Ari; Purnomo, Didik; Nte, Ngboawaji Daniel (International Law Discourse in Southeast Asia, 2024)
The transformation of international criminal justice principles into Indonesia's national criminal justice system reflects the country's commitment to aligning domestic law with global human rights and accountability standards. Indonesia, as a member of the international community, has progressively incorporated international norms and principles into its legal framework, particularly in response to the rise of international crimes such as genocide, war crimes, and crimes against humanity. The adoption of these global values in domestic law requires a nuanced approach, as Indonesia navigates its national sovereignty, cultural context, and legal traditions while integrating the broader principles of international justice. The study examines the mechanisms through which Indonesia has absorbed international criminal justice norms, focusing on key developments such as the ratification of the Rome Statute of the International Criminal Court (ICC) and the establishment of domestic legal provisions for addressing crimes under international law. It also evaluates the challenges Indonesia faces in harmonizing its criminal justice system with international standards, such as issues related to jurisdiction, the independence of the judiciary, and the political will to prosecute international crimes effectively. This paper analyzes the legal reforms in Indonesia’s national criminal justice system, exploring both the successes and limitations of these efforts. It highlights the role of international treaties, national legislation, and judicial practice in shaping a more comprehensive and fair criminal justice system. Moreover, the research emphasizes the importance of fostering international cooperation and strengthening domestic institutions to ensure the effective implementation of global principles. Ultimately, this study underscores the dynamic interaction between domestic law and international criminal justice, emphasizing the need for continuous adaptation to uphold global human rights values in a national context.